Social orientation of banking products and services - Y. A. Vasilyeva (Путеводитель предпринимателя)
The social orientation of banks activities determines the priorities for their development. The author reviews key characteristics of banking products and services, which determine their social orientation, and also offers a system of comprehensive assessment of the quality of banking products and services for society.